ESENSI DOKTRIN-DOKTRIN ESKATOLOGI DALAM HIKAYAT RAJA JUMJUMAH (Kajian Teks dan Suntingan Teks) - Dedi Supriadi (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2021)
This research is motivated by the essence of the eschatology of the doctrines in Hikayat Raja Jumjumah, which is then reduced to three problem formulations, namely; how the script and the text of Hikayat Raja Jumjumah, how the edited text of Hikayat Raja Jumjumah, and what is the essence of eschatology as a doctrine of the belief in Hikayat Raja Jumjumah. To appreciate the three points of the problem, the researcher used a philological approach to the object of research in the form of the Hikayat Rakyat Jumjumah manuscripts stored in the National Library of the Republic of Indonesia, which amounted to 5 manuscripts with a focus on the study of manuscripts with code W. 109. This type of research is descriptive analysis research. by focusing on the study of library data (library research). The results of this study found three main points, namely; first, Hikayat Raja Jumjumah is an old literary product or classical literature that still uses handwriting and uses Arabic script in Malay, which refers to the Arabic script with the title Qissah al-Jumjumah and Hadits al-Jumjumah, secondly, the text editing in this study focuses on in two ways, namely related to the transliteration of Arabic into Latin and editing marks which include the